Headache occurrence and classification among distance runners - Swain, R.; Rosencrance, G. (West Virgina Medical Journal, 1999)
There has been little research done on headaches in the athletic population. To determine the characteristics, frequency, and the effects of medication and exercise on headache in marathon runners, we conducted a random survey involving 354 male and 118 female distance runners participating in the annual 15-mile and 5 K Charleston Distance Run on August 31, 1996. Runners were classified into categories of probable migraine, possible migraine, probable tension, probable cluster and other unclassified headaches using modified International Headache Society criteria. There was a higher proportion of distance runners with migraine headaches compared to the regular population (36% vs. 17%). Running did reduce the severity and frequency of all types of headaches. Sleep eliminated headaches in most of the headache patients. The migraine group bad a statistically significant lower age (39.7) and the most headaches per month (3.1) with trends in the most numbers of runners with a previous head injury (n = 7) and the most with equipment causing headaches (n = 13). Only 5% (n = 26) of the runners had sought medical care for their headaches, however, over 180 athletes noted mild-to-moderate symptoms. Since very few runners seek medical care for headaches, physicians need to identify and treat these patients to maximize their athletic abilities.